2004
DOI: 10.1093/treephys/24.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Effects of partial defoliation on carbon and nitrogen partitioning and photosynthetic carbon uptake by two-year-old cork oak (Quercus suber) saplings

Abstract: At the end of the growing season in late July, 20-month-old cork oak (Quercus suber L.) saplings were partially defoliated (63% of leaf area) to evaluate their ability to recover leaf area after defoliation. At 18 and 127 days after defoliation, changes in starch and nitrogen pools were determined in leaves and perennial organs, and variations in photosynthetic carbon uptake were investigated. To determine the role of stored nitrogen in regrowth after defoliation, plant nitrogen was labeled in the previous win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 24 publications
2
17
1
Order By: Relevance
“…Similar results have been reported by Niinemets [36] in three temperate woody species and by Johnson et al [24] in Fagus sylvatica, but contrast to those presented by Meletiou-Christou et al [30] in four Mediterranean evergreen sclerophylls, which showed no substantial differences on soluble sugars when comparing sun and shade leaves. Changes on water availability through the growing season did not affect either soluble sugar concentration in twoyear-old cork oak seedlings grown outdoors in Portugal, although mean values are higher than ours (between 1.0 and 1.7 mg glucose·cm -2 ), probably related to seedling age [12]. The higher soluble sugar concentrations in seedlings grown under higher irradiances provoked a decrease of the osmotic potential at full turgor (Ψπ 100 ) and are at least partly responsible for osmotic adjustment [31].…”
Section: (A) (B)contrasting
confidence: 86%
“…Similar results have been reported by Niinemets [36] in three temperate woody species and by Johnson et al [24] in Fagus sylvatica, but contrast to those presented by Meletiou-Christou et al [30] in four Mediterranean evergreen sclerophylls, which showed no substantial differences on soluble sugars when comparing sun and shade leaves. Changes on water availability through the growing season did not affect either soluble sugar concentration in twoyear-old cork oak seedlings grown outdoors in Portugal, although mean values are higher than ours (between 1.0 and 1.7 mg glucose·cm -2 ), probably related to seedling age [12]. The higher soluble sugar concentrations in seedlings grown under higher irradiances provoked a decrease of the osmotic potential at full turgor (Ψπ 100 ) and are at least partly responsible for osmotic adjustment [31].…”
Section: (A) (B)contrasting
confidence: 86%
“…Seedlings have a smaller capacity for storage of assimilates than larger plants. Thus, following loss of photosynthetic area, the demand on stored carbon reserves is likely to be intense (Cesaroli et al, 2004) and result in relatively high consumption or export of assimilates. The present study suggests that insect defoliation increased export of sugars from the leaf (Tab.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of N limitation on eucalypt production are well documented (Nambiar, 1984;Sheriff and Nambiar, 1991;Pereira et al, 1992;Smethurst et al, 2003) and include reduced leaf area and stem growth (Sheriff and Nambiar, 1991;Barry et al, 2012). In defoliation studies, nitrogen remobilisation has been shown to be important in recovery in many tree species (Millard et al, 2001;Cerasoli et al, 2004) although in general, the effects of defoliation on N remobilisation in eucalypts species are poorly understood. Foliar N concentrations in E. globulus remain at similar levels to those of non-limited plants (Pereira et al, 1992;Pinkard et al, 2011b), meaning that photosynthetic capacity per unit leaf area is similar under limited and non-limited conditions.…”
Section: Water and Nutrient Effectsmentioning
confidence: 99%